Developing An Integrated Nahwu Textbook For Kitab Kuning Reading Skills - Zaenuri, Muhammad; Baroroh, R. Umi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This research aimed to develop a Nahwu textbook integrated with authentic material for kitab kuning reading skills using the Graves model. This study's research and development procedure follows Graves' instructional material development model tailored to field conditions. It is used in five stages: needs analysis, goal setting, content conceptualization, material selection, and content and activity organization. Data was collected through questionnaires from 10 students, one Nahwu teacher, and one expert, then analyzed descriptively. The results show a clear need for Nahwu books to integrate mastery of rules and classical text reading skills. According to the pesantren curriculum, this book was developed to improve Kitab Kuning's mastery of Nahwu rules and reading skills. The content is compiled based on the Nahwu Ta’limiy approach, which integrates linguistic elements to support the skills of reading the Kitab Kuning. The teaching materials are taken from Ajrumiyah's book and Kitab Kuning (Islamic classical texts), which follow the pesantren tradition. The book is arranged thematically with exercises and drill methods to reinforce learning. Expert and teacher evaluations show that this book is practical and follows the curriculum without revision. The trial on students showed explicit, relevant material and exercises to help master Nahwu and read the Kitab Kuning effectively. This study confirms that grammar learning for non-native speakers cannot be separated from other linguistic elements, such as vocabulary, or language skills, such as reading, which are the ultimate goal of language learning.